Case report: Granulocyte-macrophage colony-stimulating factor sargramostim did not rescue the neutrophil phenotype in two patients with JAGN1-mutant severe congenital neutropenia - Farmand, Susan; Aydin, Susanne Eva; Wustrau, Katharina; Böhm, Svea; Ayuk, Francis; Escherich, Gabriele; Skokowa, Julia; Müller, Ingo; Lehmberg, Kai (Frontiers in Immunology, 2024)
Background Homozygous or compound heterozygous mutations in JAGN1 cause severe congenital neutropenia. JAGN1-mutant patients present with severe early-onset bacterial infections and most have been described as low-responders to recombinant granulocyte colony-stimulating factor (G-CSF) therapy. In a murine, hematopoietic JAGN1 knockout model, which displays susceptibility to Candida albicans infection in the absence of neutropenia, treatment with granulocyte-macrophage-CSF (GM-CSF) was able to restore the functional defect of neutrophils. Patients We present two unrelated patients with biallelic JAGN1 mutations, who were both treated with subcutaneous GM-CSF (sargramostim) after treatment failure to G-CSF. The first patient was an 18-year-old pregnant woman who received GM-CSF at 12 weeks of gestation up to a dose of 10 µg/kg/d for 7 days. The second patient was a 5-month-old girl who received GM-CSF for a total of 9 days at a dose of up to 20 µg/kg/d. GM-CSF did not increase neutrophil counts in our patients. Treatment was stopped when neutrophil numbers declined further, no beneficial effect was noticed, and patients presented with infections. No adverse effects were observed in either patient and the fetus. Both patients ultimately underwent successful hematopoietic stem cell transplantation. Discussion Both patients showed a high recurrence rate of severe infections on G-CSF treatment. GM-CSF therapy did not ameliorate the clinical phenotype, in contrast to the improvement of neutrophil function observed in the JAGN1 mouse model. No major additional extra-hematopoietic manifestations were evident in our patients. Conclusion In two unrelated patients, GM-CSF did not have any beneficial effect on neutrophil counts. Patients with JAGN1-mutant SCN with reduced G-CSF responsiveness and elevated infection rate should be evaluated early for stem cell transplantation.